2019
DOI: 10.48084/etasr.2972
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer and Millimeter Wave P-to-P Links Under Dust Storm Effects in Arid Climates

Abstract: A dust storm is the main attenuation factor that can disturb receiving radio signals in arid climate condition as in Saudi Arabia. This paper presents a study on the effect of dust storms on the received radio frequency power in a homogenous environment in the city of Riyadh. A number of micrometer and millimeter wave links have been considered along with several measured dust storm data to investigate the dust storm effects. The results showed that dust storm can critically influence the communication link an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“… Microwave (MW) attenuation in Saudi Arabia. The effect of relative humidity (RH) is demonstrated by matching modeled to observed (Shamsan et al., 2019) MW attenuations assuming uncharged dry‐phase (RH = 0%) and humidified (RH = 70%) dust‐storm aerosols. …”
Section: Resultsmentioning
confidence: 95%
“… Microwave (MW) attenuation in Saudi Arabia. The effect of relative humidity (RH) is demonstrated by matching modeled to observed (Shamsan et al., 2019) MW attenuations assuming uncharged dry‐phase (RH = 0%) and humidified (RH = 70%) dust‐storm aerosols. …”
Section: Resultsmentioning
confidence: 95%
“…The contribution of this paper is the exploration of the spectrum sharing status between the HAPS and the FS in millimeter waves by assuming intersystem interference scenarios between the two systems within urban and suburban areas and with various HAPS altitudes and different terrestrial distances to connect the FS link. These interference scenarios have not been studied in the literature at millimeter waves [14,15], namely 38 and 47GHz. Consequently, some recommendations that ease spectrum sharing are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This work concluded that the moisture effect is important because it increases within the frequency, however the model ignores other atmospheric parameters accompanied by the sand and dust storm event (wind speed, wind direction, temperature, atmospheric pressure) [16]. Deployment of 5th generation (5G) telecommunication systems and the emergence of the Internet of Things (IoT) impose a challenge to study the effects of these storms on microwave and millimeter waves with particular applications in the areas of antenna theory, particle characteristics, and microwave systems performance [15]. In this study, a ML model is developed to predict the microwave signal attenuation due to atmospheric conditions recorded during dust and sand storms.…”
Section: Introductionmentioning
confidence: 99%